Lithuania in the euro area: monetary transmission and macroprudential policies - Rubio, Margarita; Comunale, Mariarosaria (Taylor and Francis, 2016)
In this paper, we develop a two-country monetary union new Keynesian general equilibrium model with housing and collateral constraints, to be calibrated for Lithuania and the rest of the euro area. Within this setting, and following the recent entrance of Lithuania in the EMU, the aim of this paper is twofold. First, we study how shocks are transmitted differently in the two regions, considering the recent common monetary policy. Then, we analyze how macroprudential policies should be conducted in Lithuania, in the context of the EMU. As a macroprudential tool, we propose a decentralized Taylor-type rule for the LTV which responds to national deviations in output and house prices. We find that, given the housing market features in Lithuania, common shocks are transmitted more strongly in this country than in the rest of the euro area. In terms of macroprudential policies, results show that the optimal policy in Lithuania with respect to the euro area may have a different intensity and that it delivers substantial benefits in terms of financial stability.